Desert determination - Yu, Bill (Survive! (Graphic Planet (Firm)), 2020)
Rob and Lillian's respective families go on an ATV vacation into the desert. Rob and Lillian decide to explore an abandoned mine but must find a way out when a cave-in blocks their path. Includes true survival stories, a desert survival guide, critical thinking question, trivia, and a glossary.